Pharmacovigilance of biosimilars – Why is it different from generics and innovator biologics? - Oza, B (J Postgrad Med, 2019)
Biosimilars are being marketed in India since 2000. Like biologics, biosimilars have a large size, complex structure, and complicated manufacturing process, and they are produced in a living organism. It requires specialized delivery devices for administration and needs tighter temperature control to prevent degradation. As biosimilar development follows abbreviated pathway, adverse events (AEs) previously unknown during a clinical trial may be detected postmarketing. In India, the awareness on pharmacovigilance has increased significantly after implementation of the pharmacovigilance guidance in January 2018. However, biologics require tighter monitoring to ensure their safety and efficacy. This review article discusses the importance of pharmacovigilance for biosimilars, how it is different from generics, and provides recommendations to sensitize clinicians and researchers about the requirement of a different approach to improve pharmacovigilance for biosimilars. Pharmacovigilance for biosimilars is as important as it is for innovator biologics and more important than that for generics.